SG-APSIC1055: Hand hygiene challenges among the ancillary team during the COVID-19 pandemic. (February 2023) - Liu, Qinnan; Devi, Kamini; Sazali, Ismail Bin; Yuen, Tan Kwee; Maroni, Shaiful Bahri; Ganotisi, King Richard Jay; Siang, Quek Bak; Lin, Ling Moi
Abstract : Objectives: Ancillary staff members perform operational support functions and play an active role in enhancing the patient care experience. Infection prevention practices among ancillary staff play a critical role in preventing transmission of microorganisms, which ensures the safety of patients. Low hand hygiene compliance was found among porters in a cross-institutional hand hygiene audit in 2021. A quality improvement team was formed to improve hand hygiene compliance, especially during the COVID-19 pandemic. Methods: A focus-group discussion and survey were conducted to understand hand hygiene knowledge and challenges among porters. Using the findings, the team initiated Glo–germ education tools, pocket alcohol hand-rub agents, pocket moisturizer, poster display, and a toolbox messaging system via conversion of group roll call to satellite-area roll call. Respective satellite teams were sent hand hygiene reminders, and prompt corrective action was taken following noncompliance events. Analytic comparisons of pre- and postsurvey data were performed using the χ 2 test, and P < .05 was regarded as statistically significant. Results: In total, 572 ancillary staff participated in the survey. Knowledge of hand hygiene practices improved significantly following the interventions, as shown in the comparison of pre- and postintervention results: knowledge of the hand hygiene steps ( P < .001), knowledge of the duration of hand rub ( P < .001), and knowledge of duration of handwashing ( P < .001). Also, 295 staff members (97.68%) stated that implementation measures increased their awareness of the importance of hand hygiene. Moreover, the hand hygiene compliance rate improved from 77.8% to 100%. There were no significant differences related to sex ( P = .089), age group ( P = .355), years of working ( P = .359), education level ( P = .268), or difficulty in reading English ( P = .906). Conclusions: Evaluating staff hand hygiene knowledge and understanding the challenges faced among porters helped toward the development of appropriate interventions and assurance of success in project.